Strangers in the sheets: how Airbnb hosts overcome uncertainty. (27th September 2021) - Ladegaard, Isak
Abstract: Uncertainty is typically viewed as an impediment to trade. I argue that in morally attuned markets, where actors seek not just economic transactions but also social connection, uncertainty contributes to market order and reproduction. Drawing on in-depth interviews with 40 Airbnb hosts, I first explain how market risks are inadequately mitigated by social credit data, that is, publicly available information about exchange partners, and by institutional safeguards, such as the platform's insurance policy. I then explain how hosts overcome remaining uncertainties by getting to know and building rapport with their guests. This emotional labor is in turn converted to meaningful social relations that motivate further hosting. In some cases, these ad hoc ties transcend the market and live on as authentic friendships.